Performance of a Point-of-Care Test Kit (Anigen Rapid®) to Diagnose Feline Immunodeficiency Virus (FIV) Infection in Domestic Cats Using Saliva Instead of Blood in Australia - Jennifer Green; Adele Scannell; Evelyn Hall; Mark E. Westman (Veterinary Sciences)
The primary aim of this study was to determine the accuracy of saliva as a proxy for blood in cats using Anigen Rapid® FIV point-of-care (PoC) kits and as an easy collection technique applicable for all veterinary clinics and shelters. A secondary aim was to report FIV prevalence in various Australian states/territories and key cat risk factors associated with FIV infection. In total, 382 cats were recruited from patients presenting to private, shelter and teaching hospital veterinary clinics in Australia. Information collected for each cat included age, sex, neuter status, postcode, and health status (‘healthy’ versus ‘sick’). The traditional blood testing technique with Anigen Rapid® was used to determine the FIV status of cats. Comparative saliva testing found 48/382 (12.5%) cats were FIV-positive. Test sensitivity for Anigen Rapid® FIV using saliva was 84.2% (48/57; 95% CI 80.6 to 87.9). Test specificity for Anigen Rapid® FIV using saliva was 100% (325/325). The two significant cat risk factors for FIV infection were sex (male) and health status (sick). In terms of demographic information, prevalence in Tasmania and the Northen Territory was reported for the first time. This study proves the ability to utilise cheap and readily available consumables for less invasive FIV testing purposes by using saliva instead of blood, for example, when screening cat before adoption in shelters and in cats prior to annual FIV re-vaccination.